RECONSTRUCTION OF ANTI-CORRUPTION EDUCATION THROUGH THE ROLE OF CROSS-RELIGIOUS LEADERS IN BENGKULU - Nelly Marhayati; Pasmah Chandra (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
The goal of this study was to learn more about the role of inter-religion leaders in Bengkulu's anti-corruption education reconstruction. Interfaith leaders can play a role not only in theology and worship, but also in imparting anti-corruption education, which is intended to mold anti-corruption behavior in society by planting such education. This study employed a qualitative, phenomenological approach as its methodology. The role of interfaith leaders in Bengkulu in shaping anti-corruption behavior in society is still limited to providing reinforcement to the congregation through the delivery of good teachings, according to the data from interviews with five participants where they are interfaith leaders. By referring to social learning theory it was known that the role of inter religion leaders in Bengkulu in forming anti-corruption attitude in the society was still limited in emphasizing the congregation through conveying goodness and sincerity. As a result, it is necessary to reconstruct anti-corruption education carried out by the inter-religion leaders by collaborating with the Religious Communication Forum and carrying out sustainable activities involving inter-religion communities.